A Critical Analysis of The Influence of Tafsir Al-Jamal In Tafsir Nur Al-Ihsan Based on Genetic Approach - YUSUFF, MOHD SHOLEH SHEH; HAJI-OTHMAN, YUSUF; ARSAD, SYAHIZA (The journal of contemporary issues in business and government, 2021)
Tafsir Nur al-Ihsan is a book in the field of Quranic exegesis written by Syeikh Muhammad Sa’id bin Umar. The Muslim community has used this book as a reference to understand the meaning of the al-Quran. However, there is a tremendous amount of denunciation done towards the book by the community due to the lack of clear resources in translating verses of al-Quran, which has confused the community on the legality of the translation done in the book. Therefore, the main objective of this research is to study and detect the original resources of the writer in the Tafsir Nur al-Ihsan, and expressing how the sources are taken from the Quranic verses. The analysis of Tafsir Nur al-Ihsan used the genetic approach which Goldman publicized in studying the origin of the resources. While carrying out the research, the researcher referred to the text from Tafsir Nur al-Ihsan and Tafsir al-Jamal and compared both texts to detect the similarities and differences. The result of the analysis proved that Syeikh Muhammad Sa’id implemented five methods; the text was referenced from Tafsir al-Jamal while finishing his work which is quoting the text, writing an abstract, removal of some of the words, adding explanation, and refuting part of the text. The research showed that Syeikh Muhammad Sa’id refers to the Tafsir al-Jamal while creating his work to strengthen the translations written. Thus, he successfully strengthens translation when the contents of the text are parallel to the reference. However, in certain places existed a text from the Tafsir Nur al- Ihsan, which contradicts Tafsir al-Jamal's content, which failed to strengthen the translation in a particular part of the text.